Impermeable brick for lining of electrolytic cell and preparation method of impermeable brick

By using anti-seepage bricks prepared with aluminum silicate mixture, the problem of the existing aluminum electrolytic cell anti-seepage materials being easily eroded in high temperature environments is solved, and better anti-seepage effect and extended electrolytic cell life are achieved.

CN119465302APending Publication Date: 2025-02-18INNER MONGOLIA JINLIAN ALUMINUM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411451016.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The anti-seepage bricks and dry anti-seepage materials of existing aluminum electrolytic cells are easily eroded by electrolytes in high temperature environments, resulting in a decrease in the life of the tank bottom. Moreover, due to the inconsistent composition and structure of the aggregate and fine powder, the anti-seepage effect is not ideal.

Method used

Aluminum silicate mixture is used as the main component of anti-seepage bricks, including saccharite, charred gemstone, sodium feldspar, potassium silicate eutectic and fine powder sintering agent, and granulation is made by mixing evenly and adding a binder. Preparation of press forming and high temperature firing.

Benefits of technology

The prepared anti-seepage bricks have good anti-permeability, corrosion resistance and high temperature resistance, which can effectively prevent electrolyte erosion, extend the service life of the electrolytic cell, and improve the electrolytic efficiency.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses an anti-seepage brick for an electrolytic cell lining and a preparation method thereof, the anti-seepage brick comprises an aluminum silicate mixture, the aluminum silicate mixture is composed of at least three of pyrophyllite, flint clay, clay, silica, albite and potassium feldspar, a potassium silicate eutectic and a fine powder sintering aid are added, the materials are uniformly mixed, a binding agent is added for granulation, mechanical pressing molding is performed, and high-temperature sintering is performed; the aluminum silicate mixture is prepared from the following raw materials in parts by weight: 50 to 75 parts of pyrophyllite, 20 to 42 parts of flint clay, 1 to 8 parts of albite and 1 to 5 parts of potassium silicate eutectic. The invention relates to the technical field of anti-seepage bricks, and particularly provides an anti-seepage brick for an electrolytic cell lining and a preparation method of the anti-seepage brick.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-seepage bricks, in particular to an anti-seepage brick for electrolytic cell lining and a preparation method thereof. Background Art

[0002] During the construction of aluminum electrolytic cells, the masonry work of the bottom is very important. This part is mainly constructed by combining heat insulation materials, refractory insulation bricks and dry anti-seepage materials. Anti-seepage materials are one of the most important processes for the overhaul of electrolytic aluminum cells. It is necessary to pre-block the refractory insulation bricks and the cathode carbon block group. Before laying the dry anti-seepage materials on the refractory insulation bricks, first make a special mold of a certain height according to the compression ratio calculated in advance and use a scraper to compact it in two layers. After the first layer is added to the calculated height and flattened with a scraper, color strips and 1mm thick cold-rolled steel plates are laid on the materials, and they are compacted with a special reciprocating sandstone rammer according to the designed route and number of times. After the first layer is completed, check whether the compacted height of the anti-seepage material reaches its compression ratio. If it is qualified, lay the second layer, and compact the anti-seepage material to the designed elevation in the same way.

[0003] After compaction is completed, 9 points are measured on the surface of the anti-seepage material according to the pre-drawn reference line for inspection. If there are some points that exceed the standard, they can be repaired to make the levelness reach ±4mm to ensure the installation size of the cathode carbon block.

[0004] The main disadvantages of this method are:

[0005] (1) During the production of electrolytic aluminum, the cell lining will be corroded by high-temperature electrolytes, and steam and aluminum liquid will penetrate the aluminum solution through the carbon brick seams into the refractory bricks and insulation bricks on the side walls, and will penetrate into the insulation layer through the carbon cathode at the bottom of the cell, greatly reducing the life of the aluminum electrolytic cell;

[0006] (2) The dry anti-seepage material is selected according to the design of the electrolytic cell. When selecting the material, it is necessary to ensure that the temperature inside the carbon cathode material is greater than 850°C, because NaF will crystallize below 850°C, causing the volume of the cathode carbon block to expand and the carbon block to expand, thus reducing the service life of the electrolytic cell.

[0007] At present, the production of anti-seepage bricks or dry anti-seepage materials requires a certain particle gradation, usually 50-70% aggregate, 30-50% fine powder, and appropriate sintering aids. Although it can react with the penetrating electrolyte to a certain extent to form an anti-seepage layer, the inconsistency between aggregate and fine powder in composition and structure leads to inconsistent reaction speeds between aggregate and fine powder and the penetrating electrolyte. Fine powder has a loose structure and reacts quickly with electrolytes, while aggregate is dense and reacts slowly. In addition, the composition of the two is different, which makes it impossible for aggregate to react synchronously with fine powder to form an anti-seepage layer, so the anti-seepage effect is not ideal.

[0008] Therefore, there is a great need for an anti-seepage brick for aluminum electrolytic cells with good anti-seepage effect, consistent composition and uniform structure. Summary of the invention

[0009] The present invention provides the following technical invention: an anti-seepage brick for electrolytic cell lining proposed by the present invention comprises an aluminum silicate mixture, wherein the aluminum silicate mixture is composed of at least three of pyrophyllite, pyrophyllite, clay, silica, albite and potassium feldspar, and is further added with potassium silicate eutectic and fine powder sintering aid, which are mixed evenly, granulated with a binder, machine pressed and sintered at high temperature.

[0010] The types and weight proportions of raw materials in the aluminum silicate mixture are: 50-75 parts of pyrophyllite, 20-42 parts of pyrophyllite, 1-8 parts of albite, and 1-5 parts of potassium silicate eutectic.

[0011] The types and weight proportions of raw materials in the aluminum silicate mixture are: 65 parts of pyrophyllite, 32 parts of pyrophyllite, 3 parts of albite, and 1 part of potassium silicate eutectic;

[0012] Furthermore, the pyrophyllite has a SiO2 content of ≥70%, an Al2O3 content of ≤26%, and a particle size of 100 meshes.

[0013] Furthermore, the SiO2 content in the coke gemstone is ≥55%, Al2O3≤45%, and the particle size is 100 mesh.

[0014] Furthermore, the SiO2 content in the albite is ≥65%, Al2O3≤20%, Na2O≤12%, and the particle size is 100 mesh.

[0015] Furthermore, the potassium silicate eutectic is a eutectic of potassium tetrasilicate and potassium disilicate, and has a particle size of 1000 mesh.

[0016] The binder for the aluminum silicate mixture is a PVA solution with a concentration of 5%-8% and an addition amount of 5.0%-7% of the weight of the aluminum silicate fine powder.

[0017] The binder for the aluminum silicate mixture is a PVA solution with a concentration of 8% and an addition amount of 5% of the weight of the aluminum silicate fine powder.

[0018] The present invention provides a method for preparing an anti-seepage brick for electrolytic cell lining, which specifically comprises the following steps:

[0019] 1) Weigh the raw materials according to the proportion and mix them evenly in a mixer for 4 hours, active material A;

[0020] 2) Pour material A into a mixer, add a PVA solution with a binder concentration of 8% in an amount of 5.0% by weight of the mixture, mix for 20 minutes, and pass through a 15-mesh sieve to obtain material B;

[0021] 3) Forming material B in a brick press with a pressure of 80 tons to obtain a brick blank;

[0022] 4) Keep the pressed bricks at 200°C for 24 hours;

[0023] 5) keeping the brick obtained in step 4 at 1150° C. for 8 hours to obtain an impermeable brick;

[0024] 6) Finished product inspection and storage.

[0025] The beneficial effects achieved by the present invention are as follows: The present invention provides an anti-seepage brick for electrolytic cell lining and a preparation method thereof,

[0026] (1) The new anti-permeability brick is used in conjunction with the anti-permeability castable as the barrier layer of the aluminum electrolytic cell, which can prevent Na, NaF and cryolite melt from further penetrating into the insulation layer, prevent the protective layer from being eroded, and make its insulation capacity last longer, thereby protecting the normal use of the electrolytic cell and improving the service life of the aluminum electrolytic cell;

[0027] (2) It can effectively protect the inner wall of the electrolytic cell, improve electrolysis efficiency and reduce production costs;

[0028] (3) High strength: The high-strength anti-seepage bricks for aluminum electrolytic cells are made of high-quality raw materials and fired at high temperatures. They have high strength and can withstand the high temperature and high pressure generated during the aluminum electrolysis process, ensuring the stability of the electrolytic cell.

[0029] (4) Anti-permeability: The high-strength anti-seepage bricks for aluminum electrolytic cells have good anti-permeability properties, which can effectively prevent the electrolyte from corroding the inner wall of the electrolytic cell, reduce the loss of electrolyte, and improve the electrolysis efficiency.

[0030] (5) Corrosion resistance: The high-strength anti-seepage bricks for aluminum electrolytic cells have high corrosion resistance and can resist the corrosion of electrolytes under high temperature and high pressure environments, thus extending the service life of the electrolytic cells.

[0031] (6) High temperature resistance: The high-strength anti-seepage bricks for aluminum electrolytic cells have a high melting point and can remain stable in high temperature environments without deformation or damage due to temperature changes;

[0032] (7) Good wear resistance: The high-strength anti-seepage bricks of aluminum electrolytic cells have good wear resistance, which can maintain a smooth surface during long-term use and reduce the number of maintenance times. DETAILED DESCRIPTION

[0033] The following will clearly and completely describe the technology in the embodiments of the present invention in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] Example 1

[0035] An anti-seepage brick for electrolytic cell lining, comprising an aluminum silicate mixture, wherein the aluminum silicate mixture comprises 65 parts of pyrophyllite, 32 parts of pyrophyllite, 3 parts of albite, 1 part of potassium silicate eutectic, and a sintering aid, mixed evenly, added with a binder for granulation, pressed by a machine and sintered at high temperature;

[0036] The SiO2 content of the pyrophyllite is ≥70%, Al2O3≤26%, and the particle size is 100 mesh; the SiO2 content of the coke gem is ≥55%, Al2O3≤45%, and the particle size is 100 mesh; the SiO2 content of the albite is ≥65%, Al2O3≤20%, Na2O≤12%, and the particle size is 100 mesh; the potassium silicate eutectic is a eutectic of potassium tetrasilicate and potassium disilicate, and the particle size is 1000 mesh;

[0037] The binder for the aluminum silicate mixture is a PVA solution with a concentration of 8% and an addition amount of 5% of the weight of the aluminum silicate fine powder.

[0038] The present invention provides a method for preparing an anti-seepage brick for electrolytic cell lining, which specifically comprises the following steps:

[0039] 1) Weigh the raw materials according to the proportion and mix them evenly in a mixer for 4 hours, active material A;

[0040] 2) Pour material A into a mixer, add a PVA solution with a binder concentration of 8% in an amount of 5.0% by weight of the mixture, mix for 20 minutes, and pass through a 15-mesh sieve to obtain material B;

[0041] 3) Forming material B in a brick press with a pressure of 80 tons to obtain a brick blank;

[0042] 4) Keeping the pressed bricks at 200°C for 24 hours;

[0043] 5) keeping the brick obtained in step 4 at 1150° C. for 8 hours to obtain an impermeable brick;

[0044] 6) Finished product inspection and storage.

[0045] Example 2

[0046] The invention discloses an anti-seepage brick for electrolytic cell lining, comprising an aluminum silicate mixture, wherein the aluminum silicate mixture comprises 55 parts of pyrophyllite, 35 parts of pyrophyllite, 9 parts of albite, 1 part of potassium silicate eutectic and a sintering aid. The mixture is uniformly mixed, a binder is added to granulate, the mixture is machine-pressed and sintered at high temperature.

[0047] The types and weight proportions of raw materials in the aluminum silicate mixture are: 50-75 parts of pyrophyllite, 20-42 parts of pyrophyllite, 1-8 parts of albite, and 1-5 parts of potassium silicate eutectic.

[0048] The SiO2 content of the pyrophyllite is ≥70%, Al2O3≤26%, and the particle size is 100 mesh; the SiO2 content of the pyrophyllite is ≥55%, Al2O3≤45%, and the particle size is 100 mesh; the SiO2 content of the albite is ≥65%, Al2O3≤20%, Na2O≤12%, and the particle size is 100 mesh; the potassium silicate eutectic is a eutectic of potassium tetrasilicate and potassium disilicate, and the particle size is 1000 mesh.

[0049] The binder for the aluminum silicate mixture is a PVA solution with a concentration of 8% and an addition amount of 5% of the weight of the aluminum silicate fine powder.

[0050] The present invention provides a method for preparing an anti-seepage brick for electrolytic cell lining, which specifically comprises the following steps:

[0051] 1) Weigh the raw materials according to the proportion and mix them evenly in a mixer for 4 hours, active material A;

[0052] 2) Pour material A into a mixer, add a PVA solution with a binder concentration of 8% in an amount of 5.0% by weight of the mixture, mix for 20 minutes, and pass through a 15-mesh sieve to obtain material B;

[0053] 3) Forming material B in a brick press with a pressure of 80 tons to obtain a brick blank;

[0054] 4) Keeping the pressed bricks at 200°C for 24 hours;

[0055] 5) keeping the brick obtained in step 4 at 1150° C. for 8 hours to obtain an impermeable brick;

[0056] 6) Finished product inspection and storage.

[0057] Example 3

[0058] The invention discloses an anti-seepage brick for electrolytic cell lining, comprising an aluminum silicate mixture, wherein the aluminum silicate mixture comprises 75 parts of pyrophyllite, 22 parts of pyrophyllite, 2 parts of albite, 1 part of potassium silicate eutectic and a sintering aid. The mixture is uniformly mixed, a binder is added to granulate, the mixture is machine-pressed and sintered at high temperature.

[0059] The SiO2 content of the pyrophyllite is ≥70%, Al2O3≤26%, and the particle size is 100 mesh; the SiO2 content of the pyrophyllite is ≥55%, Al2O3≤45%, and the particle size is 100 mesh; the SiO2 content of the albite is ≥65%, Al2O3≤20%, Na2O≤12%, and the particle size is 100 mesh; the potassium silicate eutectic is a eutectic of potassium tetrasilicate and potassium disilicate, and the particle size is 1000 mesh.

[0060] The binder for the aluminum silicate mixture is a PVA solution with a concentration of 8% and an addition amount of 5% of the weight of the aluminum silicate fine powder.

[0061] The present invention provides a method for preparing an anti-seepage brick for electrolytic cell lining, which specifically comprises the following steps:

[0062] 1) Weigh the raw materials according to the proportion and mix them evenly in a mixer for 4 hours, active material A;

[0063] 2) Pour material A into a mixer, add a PVA solution with a binder concentration of 8% in an amount of 5.0% by weight of the mixture, mix for 20 minutes, and pass through a 15-mesh sieve to obtain material B;

[0064] 3) Forming material B in a brick press with a pressure of 80 tons to obtain a brick blank;

[0065] 4) Keep the pressed bricks at 200°C for 24 hours;

[0066] 5) keeping the brick obtained in step 4 at 1150° C. for 8 hours to obtain an impermeable brick;

[0067] 6) Finished product inspection and storage.

[0068] The anti-seepage brick prepared by the present invention has a SiO2 content of 65.1%, an Al2O3 content of 31.9%, a Na2O content of 1.26%, an apparent porosity of 9.6%, a volume density of 2.25g.cm-3, a compressive strength of 65MPa at room temperature, a thermal conductivity of 1.22W (mK) at 300°C, 1.45W (mK) at 600°C, and 1.47W (mK) at 900°C; a reaction erosion area of ​​3.0cm2, and a penetration depth of ≤2.2mm.

[0069] Compared with the existing dry anti-seepage material technology, the anti-seepage bricks are made of fine aluminum silicate raw material powder. Through the processes of fine powder mixing, granulation, molding and sintering, the prepared products have good consistency in composition, uniform structure, high volume density, low apparent porosity, and react evenly with the penetrating electrolyte to quickly form an anti-seepage layer; the reaction area of ​​the penetration layer is ≤3.0cm2, and the penetration depth is ≤2.2mm, which fully meets the performance indicators of anti-seepage bricks for electrolytic cells; anti-seepage bricks can effectively improve and slow down the erosion and penetration of aluminum electrolytic cell electrolytes on anti-seepage bricks, thereby effectively solving the problem of low cell bottom life.

[0070] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, material or apparatus including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, material or apparatus.

[0071] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An anti-seepage brick for electrolytic cell lining, characterized in that: The aluminum silicate mixture comprises at least three of pyrophyllite, pyrophyllite, clay, silica, albite, potassium silicate eutectic and potassium feldspar.

2. The anti-seepage brick for electrolytic cell lining according to claim 1, characterized in that: The types and weight proportions of raw materials in the aluminum silicate mixture are: 50-75 parts of pyrophyllite, 20-42 parts of pyrophyllite, 1-8 parts of albite, and 1-5 parts of potassium silicate eutectic.

3. The anti-seepage brick for electrolytic cell lining according to claim 2, characterized in that: The types and weight proportions of raw materials in the aluminum silicate mixture are: 65 parts of pyrophyllite, 32 parts of pyrophyllite, 3 parts of albite, and 1 part of potassium silicate eutectic.

4. The anti-seepage brick for electrolytic cell lining according to claim 3, characterized in that: The pyrophyllite has a SiO2 content of ≥70%, an Al2O3 content of ≤26%, and a particle size of 100 meshes.

5. The anti-seepage brick for electrolytic cell lining according to claim 3, characterized in that: The coke gem has a SiO2 content of ≥55%, an Al2O3 content of ≤45%, and a particle size of 100 meshes.

6. The anti-seepage brick for electrolytic cell lining according to claim 3, characterized in that: The sodium feldspar has a SiO2 content of ≥65%, an Al2O3 content of ≤20%, a Na2O content of ≤12%, and a particle size of 100 meshes.

7. The anti-seepage brick for electrolytic cell lining according to claim 3, characterized in that: The potassium silicate eutectic is a eutectic of potassium tetrasilicate and potassium disilicate, and has a particle size of 1000 meshes.

8. The anti-seepage brick for electrolytic cell lining according to claim 7, characterized in that: The binder for the aluminum silicate mixture is a PVA solution with a concentration of 5%-8% and an addition amount of 5.0%-7% of the weight of the aluminum silicate fine powder.

9. The anti-seepage brick for electrolytic cell lining according to claim 8, characterized in that: The binder for the aluminum silicate mixture is a PVA solution with a concentration of 8% and an addition amount of 5% of the weight of the aluminum silicate fine powder.

10. A method for preparing the anti-seepage brick for electrolytic cell lining according to any one of claims 1 to 9, characterized in that: The specific steps include: 1) Weigh the raw materials according to the proportion and mix them evenly in a mixer for 4 hours, active material A; 2) Pour material A into a mixer, add a PVA solution with a binder concentration of 8% in an amount of 5.0% by weight of the mixture, mix for 20 minutes, and pass through a 15-mesh sieve to obtain material B; 3) Forming material B in a brick press with a pressure of 80 tons to obtain a brick blank; 4) Keeping the pressed bricks at 200°C for 24 hours; 5) keeping the brick obtained in step 4 at 1150° C. for 8 hours to obtain an impermeable brick; 6) Finished product inspection and storage.

Citation Information

Cited By

  • Thermal-insulation impermeable brick for aluminum electrolysis cell and preparation method of thermal-insulation impermeable brick

    CN121824105A